Sirolimus in the treatment of cystic lymphangioma in a pediatric patient - Inês Fidalgo Martins; Ana Cordeiro; Maria J. Paiva-Lopes (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Cystic lymphangioma (CL) is a rare benign tumor, which occurs typically during childhood, with craniofacial, cervical or axillary being the most common locations. Lymphangiomas management can be challenging due to their permeative growth throughout tissue layers. Sirolimus is an immunosuppressive and antitumor agent that can inhibit abnormal vascular proliferation by blocking the mTOR/PI3K pathway. It is typically well-tolerated, with nausea, cytopenias, and metabolic imbalances as the most significant adverse effects. We present the case of a pediatric patient in which sirolimus was used to treat a macrocytic lymphangioma, highlighting its effectiveness and safety.